Development of Regular Circle Motion Experiment System with Remote Laboratory Based IoT using Web - Riwandha Asnan; Asrizal (Department of Physics, Universitas Negeri Padang, 2023)
Along with the development of Science and Technology, learning media is very diverse. Online learning resources are one of them. The utilization of the remote laboratory in education helps to improve instruction, particularly for experimental learning. The experimental system being built is anticipated to be able to provide reading results on the web, and it has a login system, a web-based queue system, and usage time limits. The Design and Development method is the method chosen in this study. The Design and Development technique is a systematic examination of the design, development, and assessment processes with the goal of establishing an empirical foundation for the development of new or improved models as well as instructional and non-instructional tools and products. The design and development process is described, examined, and assessed in this research as it relates to the tools and products that have been created. In general, this research aims to develop experiments of uniform circular motion using an internet-based remote laboratory. The accuracy value of the experimental system obtained was an average of 98.79% with an average error percentage of 1.21%. The accuracy value of the experimental system obtained is an average of 99.08%. Testing tools for experimental activities on the accuracy of measurement results on the web with manual measurements, obtained an average percentage of measurement errors on the web of 1.25% with an average accuracy of 98.75%.